Efficacy and persistence of long-lasting microbial larvicides against malaria vectors in western Kenya highlands - Samuel C. Kahindi; Simon Muriu; Yahya A. Derua; Xiaoming Wang; Guofa Zhou; Ming-Chieh Lee; Joseph Mwangangi; Harrysone Atieli; Andrew K. Githeko; Guiyun Yan (Parasites & Vectors, 2018)
Abstract Background Chemical-based malaria vector control interventions are threatened by the development of insecticide resistance and changes in the behavior of the vectors, and thus require the development of alternative control methods. Bacterial-based larvicides have the potential to target both insecticide resistant and outdoor-biting mosquitoes and are safe to use in the environment. However, the currently available microbial larvicide formulations have a short duration of activity requiring frequent re-applications which increase the cost of control interventions. This study was designed to evaluate the efficacy and duration of activity of two long-lasting formulations of Bacillus thuringiensis var. israelensis (Bti) and Bacillus sphaericus (Bs) (LL3 and FourStar®) under field conditions in western Kenya highlands. Methods Three sites were selected for this study in the highlands of western Kenya. In each site, one hundred anopheline larval habitats were selected and assigned to one of three arms: (i) LL3; (ii) FourStar®; and (iii) untreated control larval habitats. Four types of larval habitats were surveyed: abandoned gold mines, drainage canals, fish ponds and non-fish ponds. The habitats were sampled for mosquito larvae by using a standard dipping technique and collected larvae were recorded according to the larval stages of the different Anopheles species. The larvicides were applied at manufacturers’ recommended dosage of 1 briquette per 100 square feet. Both treatment and control habitats were sampled for mosquito larvae immediately before treatment (day 0), and then at 24 hours, 3 days and weekly post-treatment for 5 months. Results Overall larval density in treatment habitats was significantly reduced after application of the two microbial larvicides as compared to the control habitats. Post-intervention reduction in anopheline larval density by LL3 was 65, 71 and 84% for 1 day, 2 weeks and 4 weeks, respectively. FourStar® reduced anopheline larval density by 60, 66 and 80% for 1 day, 2 weeks and 4 weeks, respectively. Comparisons between the treatments reveal that LL3 and FourStar® were similar in efficacy. A higher reduction in Anopheles larval density was observed in the abandoned goldmines, while drainage canals had the lowest reduction. Conclusions Both LL3 and FourStar® long-lasting microbial larvicides were effective in reducing immature stages of An. gambiae complex and An. funestus group species, with significant reductions lasting for three months post-application.